n = 2 ∑ ∞ ( n − 2 ) ! n 7 + n 6 + n 5 + n 4 + n 3 + n 2 + n + 1 = A e
Find positive integer A which satisfies the equation above.
This problem was proposed by Artan Ajredini in Romanian Mathematical Magazine
For more problems you may wish to visit my set RMM
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Method 1 Given n = 2 ∑ ∞ ( ( n − 2 ) ! n 7 + n 6 + n 5 + ⋯ + n 2 + n + 1 ) Now multiplying and dividing by n ( n − 1 ) we can deduce that ( n − 2 ) ! n 7 + n 6 + n 5 + ⋯ + n 2 + n + 1 = n ! n 9 − n ! n Hence our sum become S = n = 1 ∑ ∞ ( n ! n 9 − n ! n ) = B 9 e − B 1 e = 2 1 1 4 6 e where B 9 , B 1 are ninth and first Bells numbers.
Note: We have that j = 0 ∑ ∞ j ! x j = B n e ⟹ B 0 = e 1 j = 0 ∑ ∞ = 1 where B n is the nth Bells numbers where n ∈ Z ≥ 0 . Further the Bells numbers are generated by B n + 1 = k = 0 ∑ n B k ( k n ) ⟹ B 1 = k = 0 ∑ 0 B 0 ( 0 0 ) = 1 Set n = 1 , 2 , 3 , ⋯ , 8 B 2 B 3 B 4 B 5 B 6 B 7 B 8 B 9 = k = 0 ∑ 1 B k ( k 1 ) = 1 + 1 = 2 = k = 0 ∑ 2 B k ( k 2 ) = 1 + 3 + 1 = 5 = k = 0 ∑ 3 B k ( k 3 ) = 1 + 6 + 7 + 1 = 1 5 = k = 0 ∑ 4 B k ( k 4 ) = 1 + 1 0 + 2 5 + 1 5 + 1 = 5 2 = k = 0 ∑ 5 B k ( k 3 ) = 1 + 1 5 + 6 5 + 9 0 + 3 1 + 1 = 2 0 3 = k = 0 ∑ 6 B k ( k 3 ) = 1 + 2 1 + 1 4 0 + 3 5 0 + 3 0 1 + 6 3 + 1 = 8 7 7 = k = 0 ∑ 7 B k ( k 7 ) = 1 + 2 8 + 2 6 6 + 1 0 5 0 + 1 7 0 1 + 9 6 6 + 1 2 7 + 1 = 4 1 4 7 0 = k = 0 ∑ 8 B k ( k 8 ) = 1 + 3 6 + 4 6 2 + 2 6 4 6 + 6 9 5 1 + 7 7 7 0 + 3 0 2 5 + 2 5 5 + 1 = 2 1 1 4 7
Method 2
Given n = 2 ∑ ∞ ( ( n − 2 ) ! n 7 + n 6 + n 5 + ⋯ + n 2 + n + 1 ) Now multiplying and dividing by n ( n − 1 ) we can deduce that ( n − 2 ) ! n 7 + n 6 + n 5 + ⋯ + n 2 + n + 1 = n ! n 9 − n n Hence our sum become S = n = 1 ∑ ∞ ( n ! n 9 − n ! n ) = n = 1 ∑ ∞ n ! n 9 − e = 2 1 1 4 7 e − e = 2 1 1 4 6 e To determine the ∑ n = 1 ∞ n ! n 9 = 2 2 1 1 4 7 e we will be using following technique .Since k = 0 ∑ ∞ k ! x k = e x Now we perform differentiation with respect to x and multiply by x after each differentiation as k = 0 ∑ ∞ k ! k ⋅ x k − 1 k = 0 ∑ ∞ k ! k 2 ⋅ x k − 1 k = 0 ∑ ∞ k ! k 3 ⋅ x k − 1 k = 0 ∑ ∞ k ! k 4 ⋅ x k − 1 k = 0 ∑ ∞ k ! k 5 ⋅ x k − 1 k = 0 ∑ ∞ k ! k 6 ⋅ x k − 1 k = 0 ∑ ∞ k ! k 7 ⋅ x k − 1 k = 0 ∑ ∞ k ! k 8 ⋅ x k − 1 k = 0 ∑ ∞ k ! k 9 ⋅ x k − 1 = e x ⟹ k = 0 ∑ ∞ k ! k ⋅ x k = x e x = ( x + 1 ) e x = ( x 2 + 3 x + 1 ) e x = ( x 3 + 6 x 2 + 7 x + 1 ) e x = ( x 4 + 1 0 x 3 + 2 5 x 2 + 1 5 x + 1 ) e x = ( x 5 + 1 5 x 4 + 6 5 x 3 + 9 0 x 2 + 3 1 x + 1 ) e x = ( x 6 + 2 1 x 5 + 1 4 0 x 4 + 3 5 0 x 3 + 3 0 1 x 2 + 6 3 x + 1 ) e x = ( x 7 + 2 8 x 6 + 2 6 6 x 5 + 1 0 5 0 x 4 + 1 7 0 1 x 3 + 9 6 6 x 2 + 1 2 7 x + 1 ) e x = ( x 8 + 3 6 x 7 + 4 6 2 x 6 + 2 6 4 6 x 5 + 6 9 5 1 x 4 + 7 7 7 0 x 3 + 3 0 2 5 x 2 + 2 5 5 x + 1 ) e x Now setting x = 1 we obtain e , 2 e , 5 e , 1 5 e , 5 2 e , 2 0 3 e , 8 7 7 e , 4 1 4 0 e , 2 1 1 4 7 e .
Your problem has a typo: . . . n 3 + n + 2 + n + 1
Not a good problem. Too much emphasis on computation rather than using math theorem in this case the use of Bell numbers. This type of problem will not attract member to solve.
Log in to reply
Sorry Sir , next time I will keep in mind about it.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Bell Numbers
Similar solution with @Naren Bhandari's
S = n = 2 ∑ ∞ ( n − 2 ) ! n 7 + n 6 + n 5 + n 4 + n 3 + n 2 + n + 1 = n = 0 ∑ ∞ n ! ( n + 2 ) 7 + ( n + 2 ) 6 + ( n + 2 ) 5 + ( n + 2 ) 4 + ( n + 2 ) 3 + ( n + 2 ) 2 + n + 2 + 1 = n = 0 ∑ ∞ n ! n 7 + 1 5 n 6 + 9 7 n 5 + 3 5 1 n 4 + 7 6 9 n 3 + 1 0 2 3 n 2 + 7 6 9 n + 2 5 5 = B 7 e + 1 5 B 6 e + 9 7 B 5 e + 3 5 1 B 4 e + 7 6 9 B 3 e + 1 0 2 3 B 2 e + 7 6 9 B 1 e + 2 5 5 B 0 e = ( 8 7 7 + 1 5 ( 2 0 3 ) + 9 7 ( 5 2 ) + 3 5 1 ( 1 5 ) + 7 6 9 ( 5 ) + 1 0 2 3 ( 2 ) + 7 6 9 ( 1 ) + 2 5 5 ( 1 ) ) e = 2 1 1 4 6 e ∵ Bell number B n = e 1 k = 0 ∑ ∞ k ! k n
Therefore, A = 2 1 1 4 6 .